Mammographic Screening Interval in Relation to Tumor Characteristics and False-positive Risk by Race/Ethnicity and Age - O'Meara, Ellen S. (2013)
BACKGROUND: Biennial screening mammography retains most benefits of annual breast cancer screening with reduced harms. Whether screening guidelines based on race/ethnicity and age would be more effective than age-based guidelines is unknown. METHODS: Mammography data from the Breast Cancer Surveillance Consortium were linked to pathology and tumor databases. We identified 40-74 year-old women who had annual, biennial, or triennial screening mammography during 1994-2008. We used logistic regression to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI) of adverse tumor characteristics among 14,396 incident breast cancer cases and 10-year cumulative risks of false positive recall and biopsy recommendation among 1,276,312 noncases. RESULTS: We found no increased risk of adverse tumor characteristics associated with biennial versus annual screening in white women, black women, 40-49 year-old Hispanic women, or 50-74 year-old Asian women. Hispanic women aged 50-74 who screened biennially versus annually had increased risk of late stage (OR 1.6, 95% CI 1.0-2.5) and large (OR 1.6, 95% CI 1.1-2.4) tumors. Asian women aged 40-49 who screened biennially had elevated risk of positive lymph nodes (OR 3.1, 95% CI 1.3-7.1). No elevated risks were associated with triennial versus biennial screening. Cumulative false-positive risks decreased markedly with longer screening interval. CONCLUSION: We found limited evidence of elevated risk of adverse tumor characteristics with biennial versus annual screening, while cumulative false-positive risks were lower. However, elevated risks of late stage disease in Hispanic women and node-positive disease in younger Asian women who screened less often than annually warrant consideration and replication.